Variability in oil droplet numbers and proportions in the retinas of anole lizards - Campbell, Darlene; Loew, Ellis R. (Frontiers in Amphibian and Reptile Science, 2024)
Colored oil droplets are a common feature in the cones of almost all diurnal lizards. Using white light microscopy, three chromotypes of droplet can be identified in anoles – yellow, green and colorless. These droplets have been associated with different cone classes using microspectrophotometry. The principal member of double cones contain a yellow droplet while the accessory member contains a diffuse yellow pigment. Both members contain the LWS visual pigment. One class of large single cone contains a yellow droplet and the LWS visual pigment. The two remaining classes of large single cone contain the green droplet and either the LWS or MWS visual pigment. As such, by noting the distribution and numbers of the different droplet chromotypes, information about cone distribution, type, and number can be deduced microscopically. Retinas from three anole species (A. cristatellus, A. sagrei, and A. carolinensis) were isolated, flattened and oriented using the two foveae as landmarks. A 19-gauge needle was used to punch out six full-thickness retinal disks from identical retinal regions from both eyes of the three species. The different oil droplets were microscopically identified by color and counted. In all three species at all six retinal areas, the colorless droplets associated with the UVS and SWS single cones represented approximately 10% of the total droplets counted. However, the proportions of the yellow and green droplets were significantly different between the species. For A. cristatellus, 80% of the droplets were green while 10% were yellow. For A. sagrei approximately 85% of the droplets were yellow while only 5% were green. For A. carolinensis 50% of the droplets were yellow while 40% were green. The possible significance of these variable proportions is discussed in terms of possible effects on color vision and ecotype of the three anoles.